Pengaruh Tingkat Suku Bunga, Dana Pihak Ketiga dan Non Performing Loan Terhadap Profitabilitas Bank BUMN Indonesia - Ali, M Rama; Siyo, Kasim (Jurnal Riset Akuntansi dan Bisnis, 2024)
This study aims to analyze the influence of interest rates, third-party funds (DPK), and non-performing loans (NPLs) on the profitability of state-owned banks in Indonesia. Bank profitability is an important factor in maintaining business continuity and increasing public trust. The independent variables used in this study are interest rates, deposits, and NPLs, while the dependent variables are profitability as measured by the Return on Assets (ROA) ratio. The research method used is a quantitative approach using secondary data from the financial statements of state-owned banks for the 2013-2022 period. Data analysis was carried out using multiple linear regression to test the influence of independent variables on dependent variables. The results of the study show that interest rates have no effect on profitability, while deposits and NPLs have a positive and significant effect on the profitability of state-owned banks. These findings imply that state-owned banks need to consider appropriate policies related to interest rate management, deposits, and NPLs to increase profitability and maintain financial performance stability